Strain, coping mechanisms, and slavery: a general strain theory application - Rocque, Michael (Crime, law and social change, 2008)
General strain theory (GST) is a framework for understanding how strain, or psychological adversity, affects individuals, and how these individuals cope with strain. Researchers have generally used the theory to study contemporary crime and deviance. However, GST offers a more general perspective for the study of strain that apply to other contexts. This paper examines applicability of GST to African-American experiences during slavery in order to determine the relevance of the theory to an historical context and to shed light onto that context. Relying on primary and secondary sources from the historical record, I argue that slaves in America experienced the types of strain outlined in GST, showing how these strains affected individuals. Moreover, during the ante-bellum period, African Americans appear to have utilized the same coping strategies and resources found in GST, which helps to illustrate how and why such coping strategies were used. As a result, GST is able to offer insights into a historical context - an application of the theory neither researchers in the criminological, nor the historical literature have explored. Implications for the application of GST in other situations of confinement (e.g., the prison) are discussed.